Integration of ternary I-III-VI quantum dots in light-emitting diodes - Islas-Rodriguez, Nery; Muñoz, Raybel; Rodriguez, Jose A.; Vazquez-Garcia, Rosa A.; Reyes, Martin (Frontiers in Chemistry, 2023)
Ternary I-III-VI quantum dots (TQDs) are semiconductor nanomaterials that have been gradually incorporated in the fabrication of light emitting diodes (LEDs) over the last 10 years because of its physicochemical and photoluminescence properties such as: adequate quantum yield values, tunable wavelength emission, easy synthesis strategies, but mainly because of their low toxicity that allow them to be excellent candidates to compete with conventional Cd-Pb based QDs. This review addresses the different strategies to obtain TQDs and how synthesis conditions influence their physicochemical properties, followed by the LEDs parameters achieved using TQDs. The second part of the review summarizes on how TQDs are integrated in LEDs and WLEDs and is presented an insight in the state of the art of LEDs development using TQDs, including advantages and disadvantages and challenges to overcome.